Vascular Graft Impregnation with a Fosfomycin/Oritavancin Combination to Prevent Early Infection - Inês Cruz; Stefano Di Bella; Mario D'Oria; Cristina Lagatolla; M. Cristina L. Martins; Cláudia Monteiro (MDPI AG, 2024)
Background/Objectives: Vascular graft infections (VGIs) represent a life-threatening complication, occurring in 0.2-6% of patients following aortic prosthetic placements. Historically, the primary focus for reducing VGIs has been on prevention. Currently, antimicrobial grafts are not available on the market. This study aimed to evaluate the efficacy of combining two antibiotics, fosfomycin and oritavancin, impregnated into the commercially available GelweaveTM vascular graft as a prophylactic alternative against the most commonly implicated bacteria responsible for VGI. Methods: The antimicrobial activity of fosfomycin and oritavancin was assessed using the broth microdilution method, and a synergistic effect was demonstrated using the checkerboard assay against Staphylococcus epidermidis, methicillin-resistant Staphylococcus aureus, and vancomycin-resistant Enterococcus faecium. The antibiotics were impregnated into the commercial vascular graft through immersion, and the antimicrobial efficacy of the fosfomycin/oritavancin-impregnated graft was assessed over a period of 7 days. Results: Eradication of all microorganisms tested was achieved using impregnation solutions with concentrations of 40 mg/mL of fosfomycin and 256 µg/mL of oritavancin. Conclusions: Impregnation with the combination of fosfomycin/oritavancin proved to be a promising approach to prevent VGIs. Vascular grafts with impregnated antibiotics are not yet available on the market, and this work represents an important step toward the development of a new class of antimicrobial vascular grafts.